Теоретичні аспекти джерелознавства у науковій спадщині Мирона Кордуби - Великопольська, У. (Архіви України, 2008)
The author examines the contribution of Myron Korduba, a Ukrainian scientist and historian (1876-1947), to the development of theoretical source studies. The publication includes analysis of his “Methodology of History” which deals with sources classification.